超声乳化术中较低累计能量复合参数有助于2型糖尿病白内障患者的治疗 (Nan Fang Yi Ke Da Xue Xue Bao, 2019)
OBJECTIVE: To evaluate the effect of different cumulative energy composite parameters on the outcomes of phacoemulsification cataract surgery in patients with type 2 diabetes mellitus. METHODS: A total of 252 patients with cataract (involving 252 eyes) and type 2 diabetes mellitus received phacoemulsification cataract surgery in our hospital between January, 2017 and June, 2019. The patients were divided into group A (150 cases) and group B (102 cases) for cataract phacoemulsification with cumulative energy composite parameters of 8 and 10, respectively, and 90 nondiabetic patients received cataract phacoemulsification with a cumulative energy composite parameters of 10 served as the control. The macular thickness, best corrected visual acuity, visual acuity, and postoperative leakage in the 3 groups were evaluated at 1 week, 1 month, and 3 months after the surgery. RESULTS: The visual acuity was significantly improved after phacoemulsification better in all the 3 groups. At 3 months after the surgery, the proportions of patients with visual acuity ratio < 0.1 or >1.0, macular thickness, best corrected visual acuity and permeability differed significantly between groups A and B (P < 0.05), but not between group A and the control group (P > 0.05). At 1 month and 3 months after the surgery, the proportion of patients with visual acuity ratio < 0.1 was significantly lower and the rate of visual acuity ratio >1.0 was higher in group A than in group B. At 1 month after the operation, the total leakage rate in group A (31.1%) was higher than that in the control group (21.1%) but comparable with that in group B; at 3 months, the total leakage rates were significantly lower in group A than in group B (10.0% vs 32.4%, P < 0.05), and the leakage resulted mainly from local and diffuse permeation. CONCLUSION: Phacoemulsification can effectively improve the visual acuity of cataract patients especially in non-diabetic patients. A lower cumulative energy composite parameter achieves better outcomes in type 2 diabetic patients with cataract. The macular thickness, local infiltration and diffuse leakage can be used as indicators for assessing visual recovery and stabilization after phacoemulsification.